Groups and Monoids of Cellular Automata - Salo V (Germany, 2025)
We discuss groups and monoids defined by cellular automata on full shifts, sofic shifts, minimal subshifts, countable subshifts and coded and synchronized systems. Both purely group-theoretic properties and issues of decidability are considered.
Cellular Automata and Discrete Complex Systems. AUTOMATA 2015